Understanding SIP and VoIP: Fundamental Technologies in Modern Communication Systems - Naga Praneeth Yerram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the fundamental technologies driving modern unified communications, specifically Session Initiation Protocol (SIP) and Voice over Internet Protocol (VoIP) systems. The article analyzes SIP's technical framework and architecture, exploring its critical role in establishing, maintaining, and terminating multimedia communication sessions across IP networks. The investigation delves into VoIP's technical foundations, examining digital voice transmission processes, infrastructure components, and economic implications in enterprise deployments. Through detailed case studies of prominent platforms like Zoom and Microsoft Teams, the study illuminates practical implementation strategies and challenges in real-world scenarios. The article also addresses emerging trends, including the integration of artificial intelligence, 5G networks, and advanced security protocols, while identifying crucial areas for future research and development. The article demonstrates that SIP and VoIP technologies offer significant cost advantages and serve as catalysts for digital transformation in enterprise communications. This analysis provides valuable insights for IT professionals, system architects, and business leaders seeking to understand and leverage these technologies in their unified communication strategies.
Keywords: Session Initiation Protocol; Voice over Internet Protocol; Unified Communications Architecture; Enterprise Communication Systems; Real-time Multimedia Protocols